PENGARUH KEDISIPLINAN, BEBAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA GURU LAKI-LAKI DAN PEREMPUAN PADA SMK NEGERI 1 SIGI (STUDI PERBANDINGAN) - Amboyo, Abdul Faisal (Katalogis, 2015)
The aims of this study are: 1) to seek and analyze the simultaneous influence of discipline, workload, and jo motivation on teachers’ performance at SMK Negeri 1 Sigi Regency; 2) to seek and analyze the partial influence of discipline, workload, and job motivation on teachers’ performance at SMK Negeri 1 Sigi Regency. The sample of this study consists of 53 teachers who selected through cencus sampling technique. The hypothesis of this study tested by using multiple linear regressions.The results demonstrate that discipline, workload and job motivation simultaneously and partially have positive and significant influence on teachers’ performance at SMK Negeri 1 Sigi Regency. Differential test shows that discipline, workload and job motivation have no significant difference.